47. Dependence from dose and fractionation of late severe urinary toxicities after radical radiotherapy for prostate cancer. (December 2018) - Palorini, F.; Cicchetti, A.; Rancati, T.; Cozzarini, C.; Avuzzi, B.; Botti, A.; Cante, D.; Borca, V. Casanova; Esposti, C. Degli; Garibaldi, E.; Girelli, G.; Iotti, C.; et al.
Abstract : Purpose: Development of NTCP models of late severe urinary symptoms after radical RT for prostate cancer (PCa). Methods: Patients were enrolled in a prospective, multicentre, observational trial in 2010–2014 and treated with conventional (74–80 Gy at 1.8–2 Gy/fr) or moderately hypofractionated IMRT (65–75.2 Gy at 2.2–2.7 Gy/fr). Bladder dose-surface histograms were corrected to 2 Gy/fr equivalent doses (EQD2) and reduced to Equivalent Uniform Doses at varying α / β and n. Urethral stricture requiring urethrotomy and bleeding (assessed by the physicians) and late obstructive symptoms and incontinence (through ICIQ and IPSS questionnaires) were evaluated before RT, at its completion and every 6 months until 5 years of follow-up. Incidence of late obstructive symptoms was defined as an increase of ⩾10 points with respect to baseline in the IPSS, at least once between 6–36 months after RT; incidence of incontinence as the sum ICIQ3 + ICIQ4 > 5, with the same timing, in continent patients before RT (ICIQ3 + ICIQ4 = 0). Maximum likelihood estimation (MLE) was employed for calculating the best-fit NTCP parameters (EUD50 and k) of all symptoms. Results: 319 patients were followed for ⩾36 months with at least 3 follow-up evaluations. 27/319 (23%) patients exhibited at least one severe late urinary symptom (details in Table). Bleeding, obstructive symptoms and incontinence showed greater incidence for hypofractionation and EQD2 > 78 Gy. The highest likelihood was obtained for very low n in all cases; low α / β was found for all the endpoints except stricture. Figure shows the best-fit NTCP parameters: incontinence and bleeding curves were steeper with rising EUD. Conclusions: Incidence of late severe urinary symptoms in patients treated with IMRT for PCa was about 20%. Bladder seems to act as a serial organ and all the symptoms significantly depend on the prescribed dose. In addition, all the symptoms, except for stenosis, show a surprisingly important effect of hypofractionation.